The Role of Social Support in Achieving Work-Life Balance: A Study of Students Working in The Food and Beverage Industry - della indriyani; Endang Herliah; Wingkolatin Wingkolatin; Nur Fitri Handayani (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
Working students face challenges in balancing academic demands with the jobs they do to meet financial needs or gain practical experience. This study aims to explore the role of social support in helping students who work in the food and beverage industry in Samarinda City achieve a balance between work and academic life. This study employs a qualitative research design with a descriptive approach to explore the role of social support in achieving work-life balance among students working in the food and beverage (F&B) industry in Samarinda City. A qualitative approach was chosen because it allows for an in-depth understanding of participants' life experiences, perceptions, and social interactions within their educational and work environments. The research subjects consist of three informants, all of whom are students working part-time in the food and beverage industry. Two informants work as baristas, while one informant works as kitchen staff in local cafes and restaurants in Samarinda City. The informants were selected using purposive sampling, a sampling technique commonly used in qualitative research to select individuals who have relevant experience and can provide rich and in-depth information related to the research problem selection.subjects was based on several considerations. First, students working in the F&B sector often face irregular working hours, customer service demands, and performance pressures, making them prone to experiencing conflicts between work and study. The results of the study show that working students apply careful time management strategies to maintain a balance between their studies and work. Social support, whether from family, friends, or self-support, proved to play an important role in reducing stress and improving their well-being. Although challenges such as difficulty in managing time and heavy academic workloads remain, the emotional and practical support provided by the surrounding environment is very helpful in achieving this. This research provides insights into the importance of social support in managing the work-life balance of working students, as well as its contribution to their well-being and academic success.Keywords: Students working, social support, work-life balance, time management